Genome-Informed Multiplex Conventional PCR for Identification and Differentiation of Xanthomonas citri pv. citri Subpathotypes, the Causal Agents of Asiatic Citrus Canker - Jarred Yasuhara-Bell; Gem Santillana; Isabelle Robène; Olivier Pruvost; Mark Nakhla; Vessela Mavrodieva (PhytoFrontiers, 2023)
Asiatic citrus canker, one of the most important diseases of citrus, is caused by Xanthomonas citri pv. citri. It has high economic impact and can spread easily, and the disease is difficult to manage; it is a quarantine organism in many citrus-producing countries. X. citri pv. citri has been separated into three subpathotypes (A, A*, Aw) that differ in host range and geographical distribution, thus creating a need to differentiate subpathotypes for surveillance and disease management. Availability of useful diagnostic tools is the cornerstone of successful surveillance, quarantine, and eradication measures. In this study, a multiplex conventional PCR (cPCR) assay was developed for detection and subpathotype determination of X. citri pv. citri. Assay specificity was assessed by four different labs on a total of 146 X. citri pv. citri and 58 other Xanthomonas isolates. The assay demonstrated high analytical sensitivity, specificity, and selectivity. False negatives were observed with A Lineage 2 strains, and potential false positives were observed for X. citri pv. bilvae. Combined with a simple extraction protocol, the assay has been deployed successfully at the Plant Protection and Quarantine Plant Pathogen Confirmatory Diagnostics Laboratory. This assay has proven useful for differentiating Asiatic citrus canker subpathotypes from symptomatic citrus tissue. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.